DIRECTIONS FOR IMPROVING THE METHODOLOGICAL TRAINING OF FUTURE COMPUTER SCIENCE TEACHERS FOR THE ORGANIZATION OF EDUCATIONAL AND RESEARCH ACTIVITIES OF STUDENTS - Bostanov, Б.Ғ.; Akhmetova, Ж.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article suggests the directions of methodological improvement of the organization of educational and research activities of future computer science teachers. In the process of organizing the educational and research activities of students, various aspects of the teacher's pedagogical activity are used. These are: organization, communication and specifics of computer science education with the organization of educational and research activities. Forms the knowledge and skills of future computer science teachers related to the organization of educational and research activities of students in the process of studying computer science at school. The organization of educational and research activities of students begins with the process of preparing the teacher for the lesson and includes the importance of areas of methodological improvement that improve the quality of students' knowledge.